Analysis of errors in English predication structures in the written work of the Grade V and VI pupils of Francisco Benitez Elementary School, Manila - Rionda, Carolina San Agustin 1936- (s.n.], 1967)
This study analyzed the errors in English predication structures which frequently occur in pupils' written works in order to trace their possible causes.